Alluvial gold: METALLURGICAL BENEFIT ALTERNATIVES - Azañero Ortiz, Angel (1998)
The alluvial gold or from laundries or rivers is a major generator of jobs and wealth. Currently for your benefit artisanal methods used and in some cases heavy equipment but with very poor especially in recovery (less than 50%) results. As part of the gold that has been worked, deficiencies and lack of other methods is lost in the tailings. In this research some general concepts of gold will be from the point of view of production and its impact on our exports, study the grain size of the gravel in general and gold in particular, important parameters related to the size distribution used to recommend the most convenient and appropriate method to optimize metallurgical results. Also gravimetric amalgamate concentrated to quantify the efficiency of the method.